Panel: Care4Care: what is it about the migrant care workforce and how to improve inclusion?. (13th November 2019) - Jacob, G; Azzopardi Muscat, N; Greer, S L
Abstract: A round table comprising three panelists will discuss the topic from different perspectives. Gabrielle Jacob, WHO: The WHO Global Code of Practice on the International Recruitment of Health Personnel. How far have we come, where are we now and what's next? Natasha Azzopardi-Muscat, EUPHA President: The role of public health in raising awareness on the contribution of migrant workers to health systems Scott L Greer, European Observatory on Health Systems and Policies: Governance4Care of the migrant care workforce: what matters?